A survey of nurses’ opinions about delirium in ICU - Rajbhandari, Nikeshmani; Koirala, Naba Raj; Rajbanshi, Lalit Kumar; Arjyal, Batsalya (Birat Journal of Health Sciences, 2021)
Introduction: Delirium is underdiagnosed especially in ICU. In a study done in the Netherlands investigators found not only ICU nurses but also intensivists had difficulty in diagnosing delirium. With the impact that delirium has on patients’ health, its monitoring and detection should be considered an integral part of patient care in critical care medicine, Knowledge and attitude are one of the primary unmet needs regarding early detection and treatment of delirium. Since nurses are the first line assessors in any ward we would like to carry out this cross-sectional survey on a group of nurses.Objective: To assess the nurses’ knowledge about delirium & to compare the knowledge between those that have worked in ICU or critical care to those who haven’t.Methodology: This was a cross-sectional survey carried out at Birat medical college and teaching hospital. Here all nurses were requested to fill a questionnaire that consisted of 15 questions. A time-frame of 1 week was taken to gather the data.Results: We collected data from 124 nurses, who had varying educational degrees, Eighty-four were currently working in an ICU and 32.5% of those not working had previously worked in an ICU. Over all knowledge level for nurses was poor where 94 of 124 nurses had less than 50% scores. About 27% of those who had worked in an ICU setting had good knowledge compared to 17.5% of those who had not.  Conclusion: Training regarding delirium is required to increase identification and adequate management to decrease morbidity due to delirium.